Effects of increasing dietary wheat middlings on nursery pig performance from 15 to 50 lb - De Jong, J.A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 210 pigs (PIC 327 × 1050, initially 15.12 lb BW) were used in a 35-d trial to evaluate the effects of increasing dietary wheat middlings (midds) on growth performance of 15- to 50-lb nursery pigs. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 5 dietary treatments with 6 replications per treatment. The 5 corn-soybean meal–based diets contained 0, 5, 10, 15, or 20% midds. Pigs were fed in a 2-phase feeding program from d 0 to 14 and d 14 to 35. Diets were not balanced for energy; thus, as midds increased, dietary energy concentrations decreased. From d 0 to 14, midds had no effect on growth performance; however, from d 14 to 35, pigs fed increasing midds had decreased ADG (linear, P < 0.02) and poorer F/G (linear, P < 0 .004). Furthermore, pigs fed increasing midds had lower (linear, P < 0.05) feed cost/pig, revenue/pig, and income over feed cost (IOFC), and a tendency for increased (quadratic, P < 0.07) feed cost/lb gain. Overall (d 0 to 35), increasing dietary midds worsened F/G (quadratic, P < 0.01), driven by poorer F/G for pigs fed 15 and 20% midds. We also observed a quadratic effect (P < 0.004) for feed cost/lb gain, with inclusion rates of 0 and 20% having the highest value. Caloric efficiency responded in a quadratic manner (P < 0.01) on both an ME and NE basis with improved caloric effi¬ciencies at intermediate levels (mainly 5%) of dietary middlings compared with 0 and 20% inclusions. These data suggest that the inclusion of midds at levels up to 15% do not negatively affect performance in 15- to 50-lb nursery pigs. Although we observed a linear decrease in overall IOFC, both inclusion rates of 5 and 10% were numerically more profitable than the control.
Keywords: Swine; Growth; Nursery pig; Wheat middlings